Signet-Ring Cell Carcinoma of the Ampulla of Vater - Lianda Siregar; Imelda M Loho; Agus Sudiro Waspodo; Dwi Sri Rejeki; Fajar Firsyada; Rahmanandika Swadari; Getty Inash Nandika; Muhammad Iqbal Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Signet-ring cell carcinoma (SRCC) of the ampulla of Vater is a very rare case and only 28 cases have beed reported in the English literature. Herein, we report a 59-year-old woman with SRCC of the ampulla of Vater. She developed symptoms of obstructive jaundice at early stage of disease and underwent pylorus-preserving Whipple procedure as definitive treatment. Histopathology examination showed numerous tumor cells with intracytoplasmic mucin and eccentric nuclei. Her tumor has already invaded the serosa of duodenum, but no infiltration to the stomach, pancreas, and lymphovascular structure. Her surgical margins and regional lymph nodes were free of tumor. She was diagnosed with T2N0M0 (stage IB) SRCC of the ampulla of Vater. No adjuvant treatment was given and she has been doing well for five months after surgery.